Pharmacological Treatment of Medication-Related Osteonecrosis of the Jaw (MRONJ) with Pentoxifylline and Tocopherol - Słowik, Łukasz; Totoń, Ewa; Nowak, Aleksy; Wysocka-Słowik, Aleksandra; Okła, Maciej; Ślebioda, Zuzanna (Journal of clinical medicine, 2025)
Background: This study aimed to evaluate the efficacy of pentoxifylline and tocopherol therapy in patients with medication-related osteonecrosis of the jaw (MRONJ). Methods: During this study, 43 patients participated, including 21 women and 22 men with a mean age of 66.8 years, who showed 63 areas of osteitis altogether. The diagnosis was made based on X-ray imaging and histopathological findings. All the subjects received pharmacological treatment with pentoxifylline 400 mg and tocopherol 400 IU. The study scheme consisted of initial observation and two follow-up examinations every 5–6 months. MRONJ severity, peripheral blood parameters, and CRP levels were evaluated. The obtained results were statistically analyzed. Results: Complete remission occurred in 46% of the subjects, with a higher rate among those taking bisphosphonates intravenously compared to oral administration. The efficacy of pentoxifylline and tocopherol treatment was not influenced by gender or lesion location. Moreover, the worst response to treatment was observed in the group with the highest disease stage, as determined in the initial study. Conclusions: Pentoxifylline and tocopherol therapy in MRONJ was effective in patients taking oral and intravenous bisphosphonates, in patients with osteoporosis, and undergoing oncological treatment. This treatment approach allows surgery to be avoided or significantly reduced. The good response to pharmacotherapy observed in patients with early stages of MRONJ shows an urgent need to monitor the patients treated with bisphosphonates carefully to diagnose MRONJ at the initial phase.